Management practices and rice grain yield of farmers after participation in a joint experimentation - Awio, Thomas; Struik, Paul C.; Stomph, Tjeerd Jan (Frontiers in Sustainable Food Systems, 2022)
Low productivity of rice in Uganda is attributed to sub-optimal production practices related to soil nutrient, crop and weed management. Application of improved management practices could enhance productivity. Returning 1 year after a joint experimentation in which different components of recommended agronomic practices (RAP) for rice were tested, we assessed change in management practices and grain yield of participating farmers (participated in joint experimentation) and non-participating farmers (did not participate) with plots in the same irrigation scheme. Participating farmers belonging to the lower-yielding farmers under farmers' practice (FP) during joint experimentation improved their management practices, compared with the middle- and top-yielding farmers. Sixty-one, 24 and 7% of lower-, middle- and top-yielding farmers, respectively, weeded earlier after experimentation compared with weeding time under FP during joint experimentation. Seventy-nine percent of lower-yielding farmers used fertiliser after experimentation compared with 18% during experimentation, with a higher N rate increase than middle- and top-yielding farmers. Overall, participating farmers transplanted and weeded earlier, and applied slightly higher N rates compared with non-participating farmers. Top-yielding farmers had significantly (p = 0.03) higher grain yield, followed by middle- and lower-yielding farmers. However, lower-yielding farmers made significantly (p < 0.001) higher yield gain than middle- and top-yielding farmers. A paired t-test showed that average yield gain was 1,358 (1,027–1,689), 473 (252–695) and −91.7 (−397–213) kg ha−1, respectively, for lower-, middle- and top-yielding farmers. Participating farmers had higher grain yield (4,125 kg ha−1) than non-participating farmers (3,893 kg ha−1). Three farm types were identified that differed in application of RAP, however, with small differences in household characteristics. The farm type with higher fertiliser use in nursery and field, line transplanting, timely weeding and higher N rate had the highest grain yield. We conclude that joint experimentation had a larger effect on raising yield of lower-yielding farmers, bringing farmers closer in their management and outputs. Lack of differences among farm households could indicate that wealth is not crucial in innovation adoption in this production system.